Enhanced Eradication of Enterococcus faecalis Biofilms by Quaternized Chitosan-Coated Upconversion Nanoparticles for Photodynamic Therapy in Persistent Endodontic Infections - Zong, Bin; Li, Xue; Xu, Quanchen; Wang, Danyang; Gao, Pengyu; Zhou, Qihui (Frontiers in Microbiology, 2022)
Due to the persistent presence of Enterococcus faecalis biofilms in apical root canals, persistent endodontic infections (PEIs) have always been an intractable disease to solve. The conventional root canal disinfectants (e.g., calcium hydroxide, chlorhexidine) are arduous to scavenge the stubborn infection. With the progress of nanomedicine in the biomedical field, antimicrobial photodynamic therapy (aPDT) is emerging as a prospective anti-infective therapy for PEIs. Herein, quaternized chitosan (QCh) modified upconversion nanoparticles (UCNP)@SiO2/methylene blue (MB) are developed with enhanced antibacterial/biofilm performance for aPDT in PEIs. QCh is coated on the UCNP@SiO2/MB by testing the changes in diameter, chemical functional group, and charge. Interestingly, QCh also increases the conversion efficiency of UCNP to generate more reactive oxygen species (ROS). Furthermore, the prepared UCNP@SiO2/MB@QCh exhibits highly effective antibacterial activity against free E. faecalis and related biofilm in vitro and extracted teeth. Importantly, the additional QCh with positive charges enhance UCNP@SiO2/MB@QCh contact with E. faecalis (negative charges) through electrostatic interaction. Then, UCNP@SiO2/MB@QCh could stick close to the E. faecalis and generate ROS under the irradiation by a 980 nm laser. The in vitro cellular test shows that UCNP@SiO2/MB@QCh has acceptable cytocompatibility. Thus, UCNP@SiO2/MB@QCh could offer a novel strategy for the potential aPDT clinical applications in the treatment of PEIs.